A method for producing polyethylene wax using high-density polyethylene

By using high-density polyethylene and iron trioxide modified montmorillonite catalysts in the production process of polyethylene wax, combined with partition temperature control and magnetic separation technology, the problem of large discrete index of polyethylene wax is solved, and high Purity and narrow distribution of polyethylene waxes are prepared to improve production efficiency and product quality.

CN118664871BActive Publication Date: 2024-12-17GUANGDONG TAILI NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410690922.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-30
Publication Date
2024-12-17
Estimated Expiration
2044-05-30

AI Technical Summary

Technical Problem

The molecular bond lengths generated by polyethylene waxes during the cracking process are inconsistent, resulting in a large discrete index of molecular weight, which increases the difficulty of subsequent processing and application.

Method used

High-density polyethylene and iron trioxide modified montmorillonite are used as catalysts to control the screw speed by partitioning temperature control and adjusting the screw speed, and the cracking process of polyethylene is controlled to generate polyethylene wax with narrow molecular weight distribution and small discrete index, and pass through magnetic The catalyst is separated by a separator to improve purity.

Benefits of technology

It effectively reduces the molecular weight discrete index of polyethylene wax, improves its purity and linear distribution, reduces coke formation, and improves the efficiency and yield of the thermal cracking reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the field of polymer technology, and specifically discloses a method for producing polyethylene wax using high-density polyethylene. The method for producing polyethylene wax using high-density polyethylene comprises: putting high-density polyethylene, ferroferric oxide-modified montmorillonite, and a solvent into a plastic extruder, adjusting the temperature and screw speed of each area of ​​the plastic extruder, and finally obtaining a powdered polyethylene wax through high-speed spraying, cooling, and magnetic attraction. The preparation method of the present invention also has the advantages of being simple, convenient, and easy to industrialize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer technology, in particular to a method for producing polyethylene wax by utilizing high-density polyethylene. Background Art

[0002] Polyethylene wax (PEW) is a low molecular weight polyethylene with the characteristics of low viscosity, high melting point, good heat resistance and good lubricity. It is an important chemical raw material and is widely used in various fields.

[0003] At present, the preparation of polyethylene wax mainly includes ethylene polymerization, ethylene cracking and polyethylene by-product purification. Ethylene cracking has become a common polyethylene wax production method adopted by most manufacturers due to its low production cost, high output and simple production process.

[0004] The polyethylene cracking method usually uses polyethylene as raw material, and cracks high molecular weight polyethylene into polyethylene with a specific molecular weight under high temperature shear conditions. However, during the cracking process, the molecular chemical bonds of polyolefins are randomly broken during the thermal and shearing process, and it is not easy to control the reaction polarity, resulting in inconsistent molecular bond lengths of the generated polyethylene wax, a large molecular weight dispersion index, and a wide distribution, which easily increases the difficulty of subsequent processing and application of polyethylene wax. Therefore, there is still room for improvement. Summary of the invention

[0005] In order to reduce the discrete index of the molecular weight of polyethylene wax, the present application provides a method for producing polyethylene wax using high-density polyethylene.

[0006] In the first aspect, the present application provides a method for producing polyethylene wax using high-density polyethylene, using the following technical solution:

[0007] A method for producing polyethylene wax using high-density polyethylene comprises the following steps:

[0008] S1, set the temperature of the conveying end of the plastic extruder to 200-220°C, the temperature of the melting end to 230-250°C, and the temperature of the connecting pipe to 180-200°C, and heat and keep warm;

[0009] S2, add high-density polyethylene, ferroferric oxide-modified montmorillonite, and solvent into a plastic extruder, set the screw speed to 5-10 r / min, and continue stirring for 30-40 minutes;

[0010] S3, after stirring, the material in the plastic extruder is extruded at 0.9-1.4m 3 / s and spraying it into a cooling tank to obtain a mixture; S4, passing the obtained powdered polyethylene wax through a magnetic separator to obtain powdered polyethylene wax.

[0011] By adopting the above technical scheme, using zone temperature control, and adjusting the screw speed to control the residence time of high-density polyethylene in different reaction intervals, low molecular weight polyethylene wax is prepared; montmorillonite is used as a catalyst to improve the cracking rate of high-density polyethylene, so that the molecular weight distribution range of the generated polyethylene wax is narrower and the discrete index is smaller; at the same time, since montmorillonite has good carbon resistance, it is not easy to form coke during the reaction, resulting in a decrease in the catalytic activity of the catalyst in the subsequent reaction process, thereby affecting the progress of the thermal cracking reaction, which is conducive to the preparation of polyethylene wax with better quality. However, montmorillonite is not easy to separate from polyethylene wax as a catalyst, which easily affects the purity of polyethylene wax. Ferrous oxide is loaded on montmorillonite to prepare ferrous oxide modified montmorillonite, so that ferrous oxide modified montmorillonite has a certain magnetism, and ferrous oxide modified montmorillonite can be separated from powdered polyethylene wax by a magnetic separator in the later stage. At the same time, due to the loading of ferrous oxide, the catalytic performance of montmorillonite is further enhanced; in addition, the loaded ferrous oxide is not easy to form coke during the cracking reaction, thereby reducing the catalytic efficiency.

[0012] Preferably, the preparation method of the ferroferric oxide modified montmorillonite is as follows: S1, grinding and sieving montmorillonite; S2, placing the montmorillonite in a hexadecyltrimethyl solution, heating and stirring, and centrifugally drying to obtain an organized montmorillonite; S3, heating and stirring the organized montmorillonite, tetraethyl silicate, ferroferric oxide, and ethanol, and centrifugally drying to obtain the ferroferric oxide modified montmorillonite.

[0013] By adopting the above technical scheme, ferroferric oxide is loaded in the pores of montmorillonite, which is beneficial to improving the magnetism of montmorillonite and enabling the montmorillonite to be recovered through magnetism; at the same time, due to the addition of ferroferric oxide, it is also beneficial to further enhance the catalytic property of montmorillonite. At the same time, the loaded ferroferric oxide is not easy to form coke during the catalytic cracking of montmorillonite, which affects the efficiency of catalytic cracking.

[0014] Preferably, in S1, the sieve used for screening is 150 mesh.

[0015] By adopting the above technical solution, the ground montmorillonite is screened to screen montmorillonite with a certain particle size, which helps to increase the loading rate of ferroferric oxide and further improve the catalytic efficiency and recovery efficiency of ferroferric oxide-modified montmorillonite.

[0016] Preferably, in S3, the mass ratio of montmorillonite, tetraethyl silicate, ferrosoferric oxide and ethanol is 1:8:(1-2):1000.

[0017] By adopting the above technical scheme, the ferroferric oxide-modified montmorillonite is prepared with raw materials in a specific ratio, which is beneficial to improving the dispersibility of montmorillonite and ferroferric oxide in the solvent, so that the ferroferric oxide can fully contact with the montmorillonite, increase the loading rate of the ferroferric oxide, and further improve the catalytic efficiency and recovery efficiency of the ferroferric oxide-modified montmorillonite.

[0018] Preparation of high-loaded Fe2O4-modified montmorillonite.

[0019] Preferably, in S2, the heating temperature is 50-60°C; in S3, the heating temperature is 50-60°C.

[0020] By adopting the above technical scheme, the ferroferric oxide-modified montmorillonite is prepared at a specific reaction temperature, which is beneficial to improving the reaction efficiency and preparing the ferroferric oxide-modified montmorillonite with a high ferroferric oxide loading rate.

[0021] Preferably, the molecular weight of the high-density polyethylene is 300,000-500,000.

[0022] By adopting the above technical scheme, high-density polyethylene with a molecular weight in a specific range is used as the raw material for preparing polyethylene wax, so that it is easier to obtain polyethylene wax with high purity and good linear distribution by controlling the temperature and reaction time during the reaction process.

[0023] Preferably, the mass ratio of the ferroferric oxide modified montmorillonite to high-density polyethylene is (1-2): (98-99).

[0024] By adopting the above technical solution, the ferroferric oxide-modified montmorillonite and high-density polyethylene are added in the above mass ratio for cracking reaction, which helps to make the high-density polyethylene undergo sufficient catalytic thermal cracking reaction and improve the yield of polyethylene wax.

[0025] Preferably, the solvent is petroleum ether.

[0026] By adopting the above technical solution and using one or more of the above substances as solvents, it is helpful to make the separated and cracked products less likely to have a gel effect, thereby increasing the yield of polyethylene wax and reducing the discrete index of polyethylene wax.

[0027] In a second aspect, the present application provides a polyethylene wax, which adopts the following technical solution:

[0028] A polyethylene wax is prepared by the above method.

[0029] By adopting the above technical scheme and preparing polyethylene wax step by step according to the above steps, it is beneficial to produce polyethylene wax with high purity, narrow molecular weight distribution and small discrete index.

[0030] In summary, this application has the following beneficial effects:

[0031] 1. By adopting zone temperature control and adjusting the screw speed to control the residence time of high-density polyethylene in different reaction intervals, low molecular weight polyethylene wax is prepared; and montmorillonite is used as a catalyst, which is conducive to improving the cracking rate of high-density polyethylene, making the molecular weight distribution range of the generated polyethylene wax narrower and the discrete index smaller; at the same time, due to the good carbon resistance of montmorillonite, it is not easy to form coke during the reaction, resulting in the catalyst The catalytic activity is reduced in the subsequent reaction process, thereby affecting the progress of the thermal cracking reaction, which is conducive to the preparation of polyethylene wax with better quality. However, montmorillonite is not easy to separate from polyethylene wax as a catalyst, thereby affecting the purity of polyethylene wax. Ferrous oxide is loaded on montmorillonite to prepare ferrous oxide modified montmorillonite, which has a certain magnetism. Later, the ferrous oxide modified montmorillonite can be separated from the powdered polyethylene wax by a magnetic separator. At the same time, due to the loading of ferrous oxide, the catalytic performance of montmorillonite is further enhanced; in addition, the loaded ferrous oxide is not easy to form coke during the cracking reaction, which reduces the catalytic efficiency.

[0032] 2. By loading ferroferric oxide in the pores of montmorillonite, the magnetism of montmorillonite is improved, so that montmorillonite can be recovered through magnetism; at the same time, due to the addition of ferroferric oxide, the catalytic property of montmorillonite is further enhanced. At the same time, the loaded ferroferric oxide is not easy to form coke in the process of catalytic cracking of montmorillonite, which affects the efficiency of catalytic cracking. DETAILED DESCRIPTION

[0033] The present application is further described in detail below in conjunction with embodiments.

[0034] The raw materials of the following preparation examples, comparative preparation examples, embodiments and comparative examples are all commercially available, as follows:

[0035] The CAS number of montmorillonite is 1318-93-0;

[0036] The CAS number of ferroferric oxide is 1317-61-9;

[0037] The CAS number of petroleum ether is 8032-32-4;

[0038] The CAS number of hexadecyltrimethylammonium is 6899-10-1;

[0039] The CAS number of tetraethyl silicate is 78-10-4;

[0040] High-density polyethylene was purchased from Maoming Branch of Sinopec Corporation, model 2420H.

[0041] Preparation Example 1

[0042] A method for preparing ferroferric oxide modified montmorillonite comprises the following steps:

[0043] S1, grinding montmorillonite in a mortar and sieving it through a 150-mesh sieve to obtain powdered montmorillonite;

[0044] S2, placing the powdered montmorillonite in a 0.6M hexadecyltrimethylol solution, heating to 50°C, stirring for 5 hours, centrifuging at 5000 r / min for 5 minutes, and drying in an oven at 60°C to obtain an organic montmorillonite;

[0045] S3, add 0.1g of organized montmorillonite, 0.8g of tetraethyl silicate, and 0.1g of ferroferric oxide to 100g of ethanol, heat to 50°C, stir for 5 hours, centrifuge at 5000r / min for 5 minutes, and dry in an oven at 60°C to obtain ferroferric oxide-modified montmorillonite.

[0046] Preparation Example 2

[0047] A method for preparing ferroferric oxide modified montmorillonite comprises the following steps:

[0048] S1, grinding montmorillonite in a mortar and sieving it through a 150-mesh sieve to obtain powdered montmorillonite;

[0049] S2, placing the powdered montmorillonite in a 0.6M hexadecyltrimethylol solution, heating to 60°C, stirring for 5 hours, centrifuging at 5000 r / min for 5 minutes, and drying in an oven at 60°C to obtain an organic montmorillonite;

[0050] S3, add 0.1g of organized montmorillonite, 0.8g of tetraethyl silicate, and 0.2g of ferrosoferric oxide to 100g of ethanol, heat to 60°C, stir for 5 hours, centrifuge at 5000r / min for 5 minutes, and dry in an oven at 60°C to obtain ferrosoferric oxide-modified montmorillonite.

[0051] Preparation Example 3

[0052] A method for preparing ferroferric oxide modified montmorillonite comprises the following steps:

[0053] S1, grinding montmorillonite in a mortar and sieving it through a 150-mesh sieve to obtain powdered montmorillonite;

[0054] S2, placing the powdered montmorillonite in a 0.6M hexadecyltrimethylol solution, heating to 55°C, stirring for 5 hours, centrifuging at 5000 r / min for 5 minutes, and drying in an oven at 60°C to obtain an organic montmorillonite;

[0055] S3, add 0.1g of organized montmorillonite, 0.8g of tetraethyl silicate, and 0.15g of ferrosoferric oxide to 100g of ethanol, heat to 55°C, stir for 5 hours, centrifuge at 5000r / min for 5 minutes, and dry in an oven at 60°C to obtain ferrosoferric oxide-modified montmorillonite.

[0056] Comparative Preparation Example 1

[0057] The difference from Preparation Example 3 is that an equal amount of montmorillonite is used to replace ferrosoferric oxide.

[0058] Comparative Preparation Example 2

[0059] The difference from Preparation Example 3 is that montmorillonite is replaced by an equal amount of ferrosoferric oxide.

[0060] Example 1

[0061] A method for producing polyethylene wax using high-density polyethylene comprises the following steps:

[0062] S1, set the temperature of the plastic extruder conveying end to 200°C, the temperature of the melting end to 230°C, and the temperature of the connecting pipe to 180°C, and heat and keep warm;

[0063] S2, add 98kg high-density polyethylene, 1kg ferroferric oxide-modified montmorillonite, and solvent into the plastic extruder, set the screw speed to 5r / min, and continue stirring for 30 minutes;

[0064] S3, after the stirring is finished, the material in the plastic extruder is extruded at 0.9m 3 / s spray into the cooling tank to obtain a mixture;

[0065] S4, passing the obtained powdered polyethylene wax through a magnetic separator to obtain powdered polyethylene wax.

[0066] In this example, the ferrosoferric oxide-modified montmorillonite was prepared in Preparation Example 1; and the solvent was petroleum ether.

[0067] Example 2

[0068] A method for producing polyethylene wax using high-density polyethylene comprises the following steps:

[0069] S1, set the temperature of the plastic extruder conveying end to 220°C, the temperature of the melting end to 250°C, and the temperature of the connecting pipe to 200°C, and heat and keep warm;

[0070] S2, add 99kg high-density polyethylene, 2kg ferroferric oxide-modified montmorillonite, and solvent into the plastic extruder, set the screw speed to 10r / min, and continue stirring for 40 minutes;

[0071] S3, after the stirring is finished, the material in the plastic extruder is extruded at 1.4m 3 / s spray into the cooling tank to obtain a mixture;

[0072] S4, passing the obtained powdered polyethylene wax through a magnetic separator to obtain powdered polyethylene wax.

[0073] In this example, the ferrosoferric oxide-modified montmorillonite was prepared in Preparation Example 1; and the solvent was petroleum ether.

[0074] Example 3

[0075] A method for producing polyethylene wax using high-density polyethylene comprises the following steps:

[0076] S1, set the temperature of the plastic extruder conveying end to 210°C, the temperature of the melting end to 240°C, and the temperature of the connecting pipe to 190°C, and heat and keep warm;

[0077] S2, add 98.5 kg high-density polyethylene, 1.5 kg ferroferric oxide-modified montmorillonite, and solvent into the plastic extruder, set the screw speed to 7.5 r / min, and continue stirring for 35 minutes;

[0078] S3, after the stirring is finished, the material in the plastic extruder is extruded at 1.2m 3 / s spray into the cooling tank to obtain a mixture;

[0079] S4, passing the obtained powdered polyethylene wax through a magnetic separator to obtain powdered polyethylene wax.

[0080] In this example, the ferrosoferric oxide-modified montmorillonite was prepared in Preparation Example 1; and the solvent was petroleum ether.

[0081] Example 4

[0082] A method for producing polyethylene wax using high-density polyethylene comprises the following steps:

[0083] S1, set the temperature of the plastic extruder conveying end to 210°C, the temperature of the melting end to 240°C, and the temperature of the connecting pipe to 190°C, and heat and keep warm;

[0084] S2, add 98.5 kg high-density polyethylene, 1.5 kg ferroferric oxide-modified montmorillonite, and solvent into the plastic extruder, set the screw speed to 7.5 r / min, and continue stirring for 35 minutes;

[0085] S3, after the stirring is finished, the material in the plastic extruder is extruded at 1.2m 3 / s spray into the cooling tank to obtain a mixture;

[0086] S4, passing the obtained powdered polyethylene wax through a magnetic separator to obtain powdered polyethylene wax.

[0087] In this example, the ferrosoferric oxide-modified montmorillonite was prepared in Preparation Example 2; and the solvent was petroleum ether.

[0088] Example 5

[0089] A method for producing polyethylene wax using high-density polyethylene comprises the following steps:

[0090] S1, set the temperature of the plastic extruder conveying end to 210°C, the temperature of the melting end to 240°C, and the temperature of the connecting pipe to 190°C, and heat and keep warm;

[0091] S2, add 98.5 kg high-density polyethylene, 1.5 kg ferroferric oxide-modified montmorillonite, and solvent into the plastic extruder, set the screw speed to 7.5 r / min, and continue stirring for 35 minutes;

[0092] S3, after the stirring is finished, the material in the plastic extruder is extruded at 1.2m 3 / s spray into the cooling tank to obtain a mixture;

[0093] S4, passing the obtained powdered polyethylene wax through a magnetic separator to obtain powdered polyethylene wax.

[0094] In this example, the ferrosoferric oxide-modified montmorillonite was prepared in Preparation Example 3; and the solvent was petroleum ether.

[0095] Comparative Example 1

[0096] The difference from Example 3 is that the ferrosoferric oxide-modified montmorillonite is replaced by an equal amount of high-density polyethylene.

[0097] Comparative Example 2

[0098] The difference from Example 3 is that the montmorillonite modified by ferroferric oxide is replaced by an equal amount of montmorillonite.

[0099] Comparative Example 3

[0100] The difference from Example 3 is that the montmorillonite is modified by replacing ferrous oxide with an equal amount of ferric oxide.

[0101] Comparative Example 4

[0102] The difference from Example 5 is that in S1, the melting end temperature is set to 220°C; in S2, the screw speed is 2r / min.

[0103] Comparative Example 5

[0104] The difference from Example 5 is that in S1, the melting end temperature is set to 260°C; in S2, the screw speed is 12 r / min.

[0105] Experiment 1 Number average molecular weight and dispersion index test

[0106] The polyethylene wax prepared in the above examples and comparative examples was tested for number average molecular weight and dispersion index by high temperature gel chromatography, wherein the chromatographic column was Agilent PL gel Olexis-BLS (300*7.5mm, 10um); the guard column was Agilent PL gel Guard (50*7.5*mm, 5um); the mobile phase was 1,2,4-trichlorobenzene; the flow rate was 1.00mL / min; and the column temperature was 150°C.

[0107] The above experimental test data are detailed in Table 1.

[0108] Experiment 2 Carbon resistance (thermogravimetric test)

[0109] 2 mg of the ferroferric oxide-modified montmorillonite of the above preparation examples and comparative preparation examples were put into a crucible, the nitrogen flow rate was set to 50 mL / min, the heating rate was set to 10°C / min, and after heating to 600°C and maintaining for 3 hours, the mass of the ferroferric oxide-modified montmorillonite was measured as M, and the weight loss rate was calculated according to the following formula. The lower the weight loss rate of the ferroferric oxide-modified montmorillonite, the better the carbon resistance.

[0110] The above experimental test data are detailed in Table 2.

[0111] Table 1

[0112] Number average molecular weight Dispersion Index Example 1 2.01 1.78 Example 2 1.93 1.75 Example 3 1.82 1.70 Example 4 2.23 1.67 Example 5 2.36 1.62 Comparative Example 1 3.86 2.58 Comparative Example 2 2.12 1.68 Comparative Example 3 2.53 1.93 Comparative Example 4 2.83 2.32 Comparative Example 5 1.98 2.47

[0113] Table 2

[0114]

[0115]

[0116] According to the data comparison of Example 3 and Comparative Examples 1-3 in Table 1, Example 3 uses ferroferric oxide to modify montmorillonite, and the molecular weight step range of the prepared polyethylene wax is narrow and the discrete index is low; Comparative Example 1 replaces ferroferric oxide modified montmorillonite with an equal amount of high-density polyethylene, and the prepared polyethylene wax has a wide molecular weight distribution and a large discrete index; Comparative Example 2 replaces ferroferric oxide modified montmorillonite with an equal amount of montmorillonite, and Comparative Example 3 replaces ferroferric oxide modified montmorillonite with an equal amount of ferroferric oxide, and the prepared polyethylene wax has a wide linear range and a large discrete index, but is better than Comparative Example 1. It shows that montmorillonite and ferroferric oxide can both play a role in catalytic cracking, and loading ferroferric oxide on montmorillonite is beneficial to further improve the catalytic performance on the basis of its own catalytic effect.

[0117] According to the data of Preparation Example 3 and Comparative Preparation Examples 1-2 in Table 2, Preparation Example 3 is ferroferric oxide modified montmorillonite, and Comparative Preparation Example 1 is montmorillonite. After thermogravimetric reaction test, the weight loss rate of both does not change much, while the weight loss rate of Comparative Preparation Example 2 is higher, indicating that the loaded ferroferric oxide is not easy to form coke during the catalytic cracking of montmorillonite, which affects the efficiency of catalytic cracking.

[0118] According to the data comparison between Example 5 and Comparative Examples 4-5 in Table 1, it can be seen that by adopting zone temperature control and adjusting the screw speed to control the residence time of high-density polyethylene in different reaction intervals, it is beneficial to prepare low molecular weight polyethylene wax with a molecular weight of about 4000.

[0119] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for producing polyethylene wax using high-density polyethylene, characterized in that: The following steps are involved: S1, set the temperature of the conveying end of the plastic extruder to 200-220°C, the temperature of the melting end to 230-250°C, and the temperature of the connecting pipe to 180-200°C, and heat and keep warm; S2, add high-density polyethylene, ferroferric oxide-modified montmorillonite, and solvent into a plastic extruder, set the screw speed to 5-10 r / min, and continue stirring for 30-40 minutes; S3, after stirring, the material in the plastic extruder is extruded at 0.9-1.4m 3 / s spray into the cooling tank to obtain a mixture; S4, passing the obtained powdered polyethylene wax through a magnetic separator to obtain powdered polyethylene wax; The preparation method of the ferroferric oxide modified montmorillonite comprises the following steps: step 1, grinding and sieving montmorillonite; step 2, placing the montmorillonite in a hexadecyl trimethylol solution, heating and stirring, and centrifugally drying to obtain an organic montmorillonite; step 3, uniformly mixing the organic montmorillonite, tetraethyl silicate, ferroferric oxide, and ethanol, heating and stirring, and centrifugally drying to obtain the ferroferric oxide modified montmorillonite; In step 3, the mass ratio of montmorillonite, tetraethyl silicate, ferrosoferric oxide and ethanol is 1:8:(1-2):1000; In the step 2, the heating temperature is 50-60°C; in the step 3, the heating temperature is 50-60°C.

2. The method for producing polyethylene wax using high-density polyethylene according to claim 1, characterized in that: In the step 1, the sieve used is 150 mesh.

3. The method for producing polyethylene wax using high-density polyethylene according to claim 1, characterized in that: The molecular weight of the high-density polyethylene is 300,000-500,000.

4. The method for producing polyethylene wax using high-density polyethylene according to claim 1, characterized in that: The mass ratio of the ferroferric oxide modified montmorillonite to the high-density polyethylene is (1-2): (98-99).

5. The method for producing polyethylene wax using high-density polyethylene according to claim 1, characterized in that: The solvent is petroleum ether.

Citation Information

Patent Citations

  • Method for preparing high-density polyethylene wax by means of pyrolysis

    CN102603936A